2022
DOI: 10.3389/fmicb.2022.895687
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Network Complexity Varies With pH as a Continuum, Not a Threshold, Across the North China Plain

Abstract: There has been little study on the biogeographical patterns of microbial co-occurrence, especially in agricultural soils. Here we investigated the biogeographical patterns and major drivers of co-occurrence network topological structure, and the relative abundance of keystone taxa for soil bacterial and fungal communities using high-throughput sequencing on a set of 90 samples across a 1,092 km transect in wheat fields of the North China Plain (NCP). We found that pH was the most important environmental factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
4
8
0
1
Order By: Relevance
“…First, higher soil pH, organic matter, total phosphorus, and available phosphorus under organic fertilization contributed to the keystone taxa of bacteria and protists in the network. This is consistent with previous studies showing that these factors can reshape microbial interactive relationships and network structures by affecting keystone taxa owing to their high connectivity and closeness centrality (Banerjee et al, 2019;Yang et al, 2022). Second, higher bacterial and protist richness under organic fertilization led to a higher number and average connectivity of nodes in the organic network than in the inorganic network.…”
Section: Control Of Bacterial Fungal and Protist Community Structures...supporting
confidence: 91%
“…First, higher soil pH, organic matter, total phosphorus, and available phosphorus under organic fertilization contributed to the keystone taxa of bacteria and protists in the network. This is consistent with previous studies showing that these factors can reshape microbial interactive relationships and network structures by affecting keystone taxa owing to their high connectivity and closeness centrality (Banerjee et al, 2019;Yang et al, 2022). Second, higher bacterial and protist richness under organic fertilization led to a higher number and average connectivity of nodes in the organic network than in the inorganic network.…”
Section: Control Of Bacterial Fungal and Protist Community Structures...supporting
confidence: 91%
“…Therefore, it’s justified to infer that microbial interactions and environmental factors might have supported the persistence of beneficial bacteria in the rhizosphere, as also observed earlier in a different study ( Debnath et al., 2023 ). Similarly, in another report, Yang et al. (2022) observed an increase in interdependent groups of bacteria with high pH values.…”
Section: Discussionsupporting
confidence: 65%
“…The increased stability along with increased complexity is in accordance with the patterns observed in macroecology (Montoya et al 2006), supporting MacArthur's argument that the complexity of ecosystems begets their stability (MacArthur 1955). Decreased pH enhancing the stability and complexity of the microbial community network was also found in a soil environment (Yang et al 2022). A previous study suggested that microbial ecological network complexity and stability appeared to be more tightly associated with the microbial community functional structure and ecosystem functional processes under climate warming (Yuan et al 2021).…”
Section: Discussionmentioning
confidence: 83%